SEBDs students' perspectives on the pathways of exclusion. - Bourmpaki, Evangelia (2015)
While the number of students identified with social, emotional and behavioural difficulties rises in the UK, the number of disciplinary exclusions rises, as well. Supporting such students constitutes a huge challenge for schools, which nowadays are under pressure to secure a good position in the league tables. Permanent exclusions are used in the UK as a response to students’ extremely inappropriate behaviour. Studies have highlighted the positive and negative implications of this practice for students or have concentrated in identifying strategies that can reduce the pupils at risk of exclusion. However, not many studies have highlighted the voices of young people, who experience exclusion. The aim of this study was to give voice to students with SEBDs and ADHD, who were permanently excluded from school, and explore their perceptions, in relation to the pathways of exclusion. Interviews within the hierarchical focusing method were conducted with 8 boys with SEBDs or ADHD and the data was thematically analysed. Five themes were identified, which provided a deep insight into the participants’ experiences, emotional world and perceptions of the implications of exclusion. The findings of this study, provide support for previous literature, as it concludes that exclusion is a negative experience for students with SEBDs and even if it is sometimes associated with positive feelings, their self-esteem is impacted negatively. Relationships with teachers, peers, parents and the ethos of the educational provision are, also, found to define whether or not students are at risk of exclusion, as they impact tremendously on the students’ behaviour and motivation for learning. Key words: exclusion, SEBDs, ADHD, teachers, interviews, pupil voice, alternative provision